Integration of Communicative Arabic Learning based on Freedom Thinking Strategy - Taufik, Taufik; Nafisah, Shofi; Dimyathi, Muhammad Afifudin; Yani, Achmad (Universitas Islam Negeri Raden Intan Lampung, 2024)
Among four skills in the Arabic learning, speaking skill is the most passive skill in Arabic learning, especially in Indonesia. The role of teacher and students is the main key in the success of Arabic learning especially in speaking skills. In this research, a phenomenological qualitative research method was used to find out the description and identification of Arabic learning strategies with a focus on freedom thinking and communication. The data of this study were obtained from literature-based descriptive analysis and student response in interviews. The student response data was obtained from distributing questionnaires related to FT-CODING learning strategies. The result showed that FT-CODING strategy is efficient in improving student’s speaking skills because it focuses on freedom thinking and communication with balanced roles between teachers and students. It was in line with the behavioral theory by John B. Watson that language learning is a form of stimulus and response. It was also supported by the semiotic theory by Ferdinand De Saussure that the meaning of language is obtained directly from signfier. Furthermore, this article was expected to examine quantitatively regarding the implementation of the FT-CODING strategy in a specific school level.